Quantifying the Eudaemonic Premium and Demography in Emerging Markets - Aso, N. E.; Ewurum, N. I. (International Journal of Real Estate, 2025)
As housing preferences evolve in places like Awka and Enugu, Nigeria, due to ageing-in-place and millennial economic expansion, traditional property valuation models are nudged towards obsolescence as it struggles to keep upwith demographic preferences. The classic hedonic approach emphasizes square feet and proximity but misses the heart of eudaemonic well-beingthat make a house a home. Extant research further skips these personal contentment intangibles, leaving a crucial property valuation gap as seniors seek urban aging-in-place comfort and millennials crave co-living vibes. This study explores how eudaemonic well-being, comprising life purpose, social connection opportunities, contentment and personal achievement drives housing demand in emerging markets. Using a mixed-methods approach, we surveyed 362 residents and interviewed 40. Inferences from the results uncover a relatively high premium for social relationships (β = 0.34) and autonomy (β = 0.28) in housing demand analysis. Specifically, ageing adults, craving purpose, are willing to pay a 22% premium, while millennials, seeking community, offer 18%. Empirical evidence highlighting how age and lifestyle amplify these preferences challenge the old-school focus on square footage and proximity that dominate hedonic valuation models. Our findings echo empirical voices pushing for a valuation rethink; one that blends market with human thriving constructs. The implications of the study suggest to practitioners and policymakers that it is not just about buildings; it is about homes that uplift lives and sustain communities in a fast-changing world.
Keywords: Eudaemonic Well-Being; Millennials; Property Valuation; Senior Citizens; Social Sustainability; Willingness-to-Pay